2015
DOI: 10.3892/ijo.2015.2956
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hMOF, but not HDAC4, is responsible for the global histone H4K16 acetylation in gastric carcinoma

Abstract: Increasing evidence suggests that the alteration of global histone H4K16 acetylation (H4K16ac) may be involved in several types of cancer. It is known that the global histone H4K16ac level in cells is controlled by several enzymes including histone acetyltransferases (HATs) and histone deacetylases (HDACs). We report in detail which particular enzyme is responsible for global reduction of histone H4K16ac in gastric cancer. Our study included 156 frozen tissue samples of primary diagnosed gastric cancer tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Accordingly, a number of more recent studies have established that the KAT responsible for H4K16ac, MOF, is expressed at low levels in a range of cancers, including breast 170 , ovarian 171 , colorectal 172 , renal 172 , gastric 172,173 and hepatocellular cancers 174 . Similar to H4K16ac, low MOF levels correlate with poor prognosis and increased metastasis [170][171][172][173][174] . The significance of low H4K16ac and MOF levels in cancer remains to be determined as, counterintuitively, MOF is required for cell proliferation in mammalian cell culture systems 31 .…”
Section: Diencephalonmentioning
confidence: 99%
“…Accordingly, a number of more recent studies have established that the KAT responsible for H4K16ac, MOF, is expressed at low levels in a range of cancers, including breast 170 , ovarian 171 , colorectal 172 , renal 172 , gastric 172,173 and hepatocellular cancers 174 . Similar to H4K16ac, low MOF levels correlate with poor prognosis and increased metastasis [170][171][172][173][174] . The significance of low H4K16ac and MOF levels in cancer remains to be determined as, counterintuitively, MOF is required for cell proliferation in mammalian cell culture systems 31 .…”
Section: Diencephalonmentioning
confidence: 99%
“…Reduced H4K16ac is strongly associated with a wide range of malignancies . Consistently, independent studies have reported MOF to be downregulated in a panel of cancer types including breast cancer , ovarian epithelial cancer , colorectal carcinoma , gastric cancer , hepatocellular carcinoma , and medulloblastoma . How the downregulation of MOF and H4K16ac drives tumorigenesis remains unknown, as paradoxically, depletion of MOF leads to cell cycle arrest in primary cell culture systems .…”
Section: Nsl Complex In Human Health and Diseasementioning
confidence: 87%
“…Our results, by showing higher hMOF protein and H4K16ac levels in HCC with mVI, suggest a transcription activation of key genes involved in cell invasion in these tumours. On the other hand, several studies have shown that hMOF was downregulated in various tumours, such as gastric cancer, breast cancer and medulloblastoma vs the non‐tumour counterpart. Altogether, these findings suggest that hMOF may play various roles depending on the tumour type.…”
Section: Discussionmentioning
confidence: 99%